Macierzyństwo w perspektywie filozoficznej, społecznej i indywidualnej. Analiza teoretyczna na podstawie literatury przedmiotu - Gregorczuk-Prosicka, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
Motherhood is the subject of analyses by many researchers, most often it remains in the area of interest of demographers, psychologists, sociologists or pedagogues. Pedagogical literature describes this issue extensively, among others in the context of family pedagogy, social pedagogy, but also in developmental or care and educational pedagogy. This study, which is a review of the literature in the social sciences, particularly in the field of pedagogy, is an attempt to discuss three perspectives: the philosophical one, in the context of motherhood as a value; the social one, concerning the practical image of motherhood and the individual perspective, understood as an woman’s individual experience and understanding of motherhood. The modern woman is constantly expanding her range of social roles, which is reflected in the scope of her duties and responsibilities. Numerous theoretical or popular studies and publications, as well as empirical studies, treat motherhood not only as a social role, but above all as a multidimensional experience. What emerges from the analyses presented below is a picture of contemporary motherhood as a complex phenomenon, constantly topical and changing, popular in both scientific discourse and social discussion, but above all as a unique, individual experience of a woman who ensures the continuity of the human species.